Linking agriculture and tourism : a qualitative study on the status and perspectives of the Kazbegi region in the Greater Caucasus - Hüller, Sarah; Justus Liebig University Giessen (My University, 2019)
After the break-up of the Soviet Union and a turning away from large-scale and often highly subsidized agriculture, today many rural regions in Georgia are characterized by subsistence agriculture. This also applies to the Kazbegi region, a mountainous region in the Greater Caucasus of Georgia. During Soviet times and at the beginning of the transition period, the main agricultural activities were vegetable production in greenhouses (based on gas supply from Russia) and livestock husbandry. With the break-up of the Soviet Union this situation has changed. Today, there are mainly small-scale agri-food producers and only a few market-oriented farmers. However, during the last decade, tourism in the Kazbegi has also been on the rise. The growth in tourism could provide opportunities for small-scale agri-food producers to increase their income by marketing their surplus production to the tourism sector and thereby improve their livelihoods. Against this background, this dissertation analyzes the current status and perspectives for linking agriculture and tourism in the Kazbegi region, among other things through an analysis of the agri-food chain. The results show hurdles for linking the sectors (such as a low agricultural production efficiency or noncompliance with food safety standards) but also potential ways how small-scale agri-food producers could market their products to the tourism sector in order to improve their income generation. In addition, with the help of a best case scenario and a worst case scenario potential future perspectives of the Kazbegi region are developed. The best case scenario shows a multi-sectoral development with agriculture and tourism in the region which reduces the risk of dependencies from only one sector and contributes to a sustainable development of the region. The worst case scenario depicts a mono-sectoral development with no agricultural production in the long term and heavy dependency on tourism, which is not recommendable. In order to reach a multi-sectoral development with incentives to work in the agricultural sector, more support for agri-food producers would be needed, for example through consultancy or access to finance. The conceptual framework of the study is provided by the theory of cultural lag of William F. Ogburn. As a methodological approach a qualitative research design has been chosen. Encompassing exploratory interviews and focus group discussions with the local population as well as expert interviews, it allows an analysis of the topic of interest from various angles. The study is embedded in the broad field of multi-sectoral, bottom-up rural development approaches that aim to improve the livelihoods of small-scale agri-food producers.The study was developed within the framework of the project AMIES II - Scenario development for sustainable land use in the Greater Caucasus, Georgia which was funded by the VolkswagenStiftung and implemented by the Center for international Development and Environmental Research (ZEU) of the Justus Liebig University Giessen in cooperation with three Georgian Universities.

Nach dem Zerfall der Sowjetunion und der Abkehr von teils hoch subventionierten Formen der Landwirtschaft sind viele ländliche Regionen in Georgien heute von Subsistenzlandwirtschaft geprägt. Dies gilt auch für die Bergregion Kazbegi im Großen Kaukasus in Georgien. Während der Sowjetzeit und zu Beginn des Transformationsprozesses waren die wichtigsten landwirtschaftlichen Aktivitäten in der Region der Anbau von Gemüse in Gewächshäusern (basierend auf der kostenlosen Versorgung mit Gas aus Russland) und die Viehhaltung. Heute gibt es nur wenige marktorientierte Landwirte in der Region, und die landwirtschaftlichen Aktivitäten zielen zumeist auf die eigene Versorgung mit Lebensmitteln ab. In den letzten Jahren ist jedoch auch der Tourismus in der Region stark gewachsen. Dieses Wachstum könnte den Kleinbauern in der Region Chancen eröffnen, ihre Produkte an den Tourismussektor zu verkaufen und so zusätzliches Einkommen zu erzielen. Vor diesem Hintergrund ist das Ziel dieser Dissertation, den aktuellen Stand von Landwirtschaft und Tourismus in der Region zu analysieren und Perspektiven zur Verknüpfung beider Sektoren in der Region Kazbegi zu entwickeln. Unter anderem wurde zu diesem Zweck die Produktions- und Dienstleistungskette regionaler Lebensmittel untersucht. Die Ergebnisse zeigen, dass für eine erfolgreiche Verknüpfung beider Sektoren verschiedene Hindernisse (wie z.B. geringe landwirtschaftliche Erträge oder die Nicht-Einhaltung von Lebensmittelsicherheitsstandards) überwunden werden müssten. Darüber hinaus zeigt die Studie aber auch potenzielle Wege zur Vermarktung regionaler Produkte an den Tourismussektor auf. Die Perspektiven der Region Kazbegi werden anhand von zwei Szenarien entwickelt und diskutiert. Das Best-Case-Szenario zeigt eine multisektorale Entwicklung mit Landwirtschaft und Tourismus in der Region auf. Dadurch verringert sich die Abhängigkeit von einem Sektor und eine nachhaltige Regionalentwicklung ist möglich. Das Worst-Case-Szenario stellt eine monosektorale Regionalentwicklung dar, bei der die Landwirtschaft verdrängt wird und eine starke Abhängigkeit vom Tourismus besteht. Um eine multisektorale Entwicklung zu erreichen, in der Anreize bestehen, in der Landwirtschaft aktiv zu sein und regionale Produkte zu vermarkten, wäre eine stärkere Unterstützung der Landwirte in der Region erforderlich, beispielsweise durch Beratungsangebote oder den Zugang zu geeigneten Finanzmitteln.Der konzeptionelle Rahmen der Studie ist durch die Theorie der kulturellen Phasenverschiebung von William F. Ogburn gegeben. Die empirischen Daten wurden mit Hilfe eines qualitativen Forschungsdesigns erhoben. Anhand von explorativen Interviews und Fokusgruppendiskussionen mit der lokalen Bevölkerung sowie Experteninterviews konnte das Forschungsthema aus verschiedenen Blickwinkeln beleuchtet und analysiert werden. Die Studie lässt sich in das breite Feld multisektoraler Bottom-Up-Ansätze zur ländlichen Regionalentwicklung einbetten, die darauf abzielen, die Einkommensmöglichkeiten von Kleinbauern zu verbessern. Die vorliegende Dissertation ist im Rahmen des von der VolkswagenStiftung finanzierten, interdisziplinären Forschungsprojekts AMIES II - Scenario development for sustainable land use in the Greater Caucasus, Georgia entstanden, das am Zentrum für internationale Entwicklungs- und Umweltforschung (ZEU) der Justus-Liebig-Universität Gießen in Kooperation mit drei georgischen Partneruniversitäten durchgeführt wurde.
Keywords: qualitative Forschung; ländliche Entwicklung; Landwirtschaft; Tourismus; Großer Kaukasus; qualitative research; rural development; agriculture; tourism; Greater Caucasus; ddc:630